The Effect of Profitability, Leverage, Liquidity, Size, and Company Growth on the Dividend Payout Ratio in the Indonesian Capital Market 2013-2018 - Azhariyah, Anjumul; Witjaksono, Andre Dwijanto; Hartono, Ulil (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine and analyze the effect of Profitability, Leverage, Liquidity, Size, and Company Growth on Dividend Payout Ratio in the Indonesian capital market 2013-2018. The population of this research is 525 companies from all sectors listed on the IDX except for the finance sector. By using purposive sampling method, the number obtained is 10 companies. The data testing method used is multiple linear regression analysis. The results showed that simultaneously the variables of profitability, leverage, liquidity, size and company growth had no effect on the dividend payout ratio. Partially, profitability, leverage, liquidity, company size have no effect on the dividend payout ratio, while the company growth variable has a significant negative effect on the dividend payout ratio.